Role of myocardial inflammation and fibrosis in the development of ventricular arrythmias in patients with inflammatory cardiomyopathy (results of 1-year follow-up). (25th November 2020) - Kovalenko, V; Nesukay, E; Cherniuk, S; Kirichenko, R; Kozliuk, A; Giresh, I
Abstract: Background: Myocardial inflammatory and fibrotic changes are the most frequent and significant causes of ventricular rhythm disorders that could result in development of life threatening arrythmias and increase the risk of sudden cardiac death, especially in young patients with inflammatory cardiomyopathy (ICM). The purpose – to estimate association of myocardial inflammation and fibrosis with development of ventricular arrythmias in patients with ICM during 12-months of follow-up. Material and methods: The study was performed on 70 patients with ICM, average age was (35, 2±2, 7) years. Initially all patients had cardiomegaly with reduced left ventricular (LV) ejection fraction - <40% and absolute value of longitudinal global systolic strain <9, 0%. By 24-hour ECG monitoring we studied frequency of ventricular premature beats (VPB) and incidence of non-sustained ventricular tachycardia (NSVT) paroxysms. All patients underwent for cardiac MRI with evaluation of early T1- and T2-weighted images for the detection of inflammatory changes and T1-weighted delayed images for detection of myocardial fibrosis. Results of cardiac MRI were estimated by Lake Louise criteria and also we performed quantification of segments involved according to standard 17-segment LV model. Initial examination was carried out within the 1st month from the clinical onset of disease and subsequent evaluation of studied parameters was performed after 12 months of follow-up. Results: After 12 months of follow-up average frequency of VPB reduced to (1, 42±0, 14) % from (2, 32±0, 27) % on initial examination (p<0, 01), similarly reduced the incidence of NSVT paroxysms – to 11, 4% after 12 months from 28, 6% initially. Mean quantity of LV segments, affected by inflammatory process and characterized by presence of edema and/or hyperemia, reduced to (2, 12±0, 22) segm. after 12 months of follow up from (6, 12±0, 71) segm. on the 1st month (p<0, 01). Also we observed increase of LV segments amount with the presence of delayed enhancement which indicates myocardial fibrosis – from (2, 04±0, 21) segm. on initial examination to (4, 79±0, 38) segm. after 12 months (p<0, 01). Using binary regression analysis we defined that initial presence of inflammatory lesions in ≥5, 0 LV segments was associated with frequent VPB (≥1, 0%) and NSVT paroxysms. Wherein, after 12 months presence of inflammatory lesions had no association with ventricular rhythm disorders but the same relation was observed between the presence of delayed enhancement in ≥4, 0 LV segments and frequent VPB (≥1, 0%) as also with NSVT paroxysms. Conclusion: At the time of clinical onset of inflammatory cardiomyopathy ventricular rhythm disorders (particularly VPB and NSVT paroxysms) were associated with larger quantity of LV segments involved into inflammatory process. After 12 months of follow-up ventricular rhythm disorders were associated predominantly with the presence of fibrotic lesions in several (≥4, 0) segments of LV. Funding Acknowledgement: Type of funding source: None